Exploring immunotherapy with antibody-drug conjugates in solid tumor oncology - Malemnganba T.; Pandey A.K.; Mishra A.; Mehrotra S.; Prajapati V.K. (My University, 2025)
Immunotherapy has emerged as a hallmark of hope in the formidable battle against solid tumors such as breast cancer, colorectal cancer, etc., with antibody-drug conjugates (ADCs) starting a new era of precision medicine. This chapter delves into the dynamic landscape of immunotherapeutic strategies, focusing on the transformative potential of ADCs. ADCs represent a combination of chemotherapy and immunotherapy, more innovative chemotherapy. We emphasize the intricate interplay between tumor biology and therapeutic intervention, uncovering the mechanisms underlying ADC efficacy and the hurdles they must overcome. Each facet of ADC development is carefully examined, from the delicate balance between payload potency and safety to the quest for enhanced tumor penetration. We also elucidate the synergistic potential of combining ADCs with existing modalities, including chemotherapy and radiation therapy, to amplify therapeutic outcomes while mitigating adverse effects. As we navigate the complexities of solid tumor oncology, a profound understanding of the immunotherapeutic potential of ADCs is gained, offering hope for a cure for patients and clinicians alike. Henceforth, we delve into this transformative journey as we advance in solid tumor treatment regimens using immunotherapy with ADCs, poised at the forefront of oncological innovation. © 2025